The prognostic value of tumor-associated macrophages detected by immunostaining in diffuse large B cell lymphoma: A meta-analysis - Lin, Mei; Ma, Shupei; Sun, Lingling; Qin, Zhiqiang (Frontiers in Oncology, 2023)
Abstract Background: The prognostic implication of tumor-associated macrophages (TAMs) in the microenvironment of diffuse large B cell lymphoma (DLBCL) remains controversial. Methods: A systematic and comprehensive search of relevant studies was performed in PubMed, EMBASE and Web of science databases. The quality of the included studies was estimated using Newcastle-Ottawa Scale (NOS). Results: Twenty-three studies containing a total of 2992 DLBCL patients were involved in this study. They were all high-quality studies scored ≥ 6 points. High density of M2 TAMs in tumor microenvironment significantly associated with both advanced disease stage (OR= 1.937, 95% CI: 1.256-2.988, P = 0.003) and unfavorable overall survival (OS) (HR = 1.750, 95% CI: 1.188-2.579, P = 0.005) but not associated with poor progression free survival (PFS) (HR = 1.672, 95% CI: 0.864-3.237, P = 0.127) and international prognostic index (IPI) (OR= 1.705, 95% CI: 0.843-3.449, P = 0.138) in DLBCL patients. No significant correlation was observed between the density of CD68+ TAMs and disease stage (OR= 1.433, 95% CI: 0.656-3.130, P = 0.366), IPI (OR= 1.391, 95% CI: 0.573-3.379, P = 0.466), OS (HR=0.929, 95% CI: 0.607-1.422, P = 0.734) or PFS (HR= 0.756, 95% CI: 0.415-1.379, P = 0.362) in DLBCL patients. Conclusion: This meta-analysis demonstrated that high density o M2 TAMs in the tumor microenvironment was a robust predictor of adverse outcome for DLBCL patients.